Agent w „Kulturze” pożądany. Nie urzeczywistniony plan zwerbowania przez wywiad PRL Mariana Pankowskiego - Tarka, Krzysztof (Archiwum Emigracji, 2012)
In the second half of the 50’s of the 20th century the intelligence of the People’s Republic of Poland intended to enlist Marian Pankowski (1919–2011), a writer, living in Belgium after World War II and cooperating with the Parisian Kultura. The main aim of the enlistment was to gain an informant in the circle connected with Kultura. In 1958 Pankowski came to Poland for the first time after years of absence (his mother lived in Sanok). As it results from the documents, the plan of enlisting him remained only on paper, in that period he also ceased to cooperate with Kultura.